Volatility effects of institutional trading in foreign stocks - Chiyachantana, Chiraphol N.; Jain, Pankaj K.; Jiang, Christine; Wood, Robert A. (Journal of Banking & Finance, 2006)
This paper examines the impact of institutional trades on volatility in international stocks across 43 countries. There is a temporary volatility spike during the trade execution period, merely reflecting the price impact costs faced by the institutions. Cross sectional regressions suggest that trade imbalances, enforcement of insider trading laws, stock prices, and an emerging market classification are positively associated with temporary volatility increases whereas the presence of market makers and better shareholders’ rights dampen such increases. In the long term, institutional trades do not destabilize markets as the levels of volatility after their trades are almost identical to their pre-decision levels.